PENGELOLAAN TATA USAHA DALAM MENINGKATKAN PELAYANAN ADMINISTRASI DI MA PLUS KETERAMPILAN HASYIM ASY’ARI TAGALDLIMO KABUPATEN BANYUWANGI TAHUN 2023/2024 - Andi Setiawan (Journal of Pedagogi, 2024)
Administrative management is the management of data and information that goes in and out of educational institutions / organizations, so that the whole series of receiving, recording, clarifying, processing, storing, typing, duplicating, sending written information and required by the institution and institution / educational organization. School administration has an important role in the smooth administration of schools, for this reason administration needs attention because it has a strategic role abd function. The purpose of this study is to find out how administrative management improves administrative services at the aliyyah madrasa plus the skills of Hasyim Asy'ari Tegaldlimo, to find out the implementation of administration in improving administrative services at the Aliyyah Madrasa plus the skills of Hasyim Asy 'ari tegaldlimo, to find out the administrative constraints to improve administrative services at the aliyyah madrasa plus skills of hasyim asy'ari tegaldlimo. In this study using a type of qualitative research with a descriptive approach. With data collection teaching techniques, there are more interviews, observations and documentation. The results of this study indicate that: first , administrative management in ma plus Hasyim Asy'ari tegaldlimo skills is carried out with the madrasah head providing direction, enthusiasm, motivation in carrying out his duties and responsibilities. Every time there is an activity in the planning and committee the employees are accompanied by an SK, when making decisions the head of the madrasah invites the employees to hold meetings and deliberations to make decisions and be mutually agreed upon. Second, the implementation of administration in improving administrative services has been going well in accordance with ma planning plus the skills of Hasyim Asy'ari Tegaldlimo. Third, the obstacles that occur in administrative management and improving administrative services in ma plus the skills of Hasyim Asy'ari Tegaldlimo, namely: obstacles in completing EMIS tasks and so on can only be done at night because during the day the wifi is weak due to the large number of users, vulnerable to short time completion of tasks when entering student data, lack of confirmation from the head if the madrasah with employees, usually the head of the madrasah fogets to conveyed to employees and it should be done immediately, there is no professional training for employees from the government.